2021
DOI: 10.1002/pa.2717
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of innovation in the relationship between organizational culture and organizational performance in Pakistan's banking sector

Abstract: This study explores the mediating role of innovation in the relationship between the dimensions of organizational culture and organizational performance. The study used questionnaire data taken from 250 managers of banks in Pakistan. Structural equation modeling was used to test hypotheses. The results indicate that while the dimensions of organizational culture and innovation have a clear and positive influence on organizational performance, organizational culture and mission have an insignificant relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 146 publications
(222 reference statements)
2
35
0
Order By: Relevance
“…Convergent validity is the degree to see which variables’ items measure the same variable [ 125 ]. According to [ 126 ], convergent validity evaluates if all constructs’ items accurately represent their accompanied predictor. Convergent validity was assessed in order to identify two techniques: average variance extracted (AVE), and composite reliability (CR).…”
Section: Results and Data Analysismentioning
confidence: 99%
“…Convergent validity is the degree to see which variables’ items measure the same variable [ 125 ]. According to [ 126 ], convergent validity evaluates if all constructs’ items accurately represent their accompanied predictor. Convergent validity was assessed in order to identify two techniques: average variance extracted (AVE), and composite reliability (CR).…”
Section: Results and Data Analysismentioning
confidence: 99%
“…Barney (1991) discussed the internal and external environments, which is also a highlight of RBV. The internal environment represents the II and external environment characterizes as EK gained from customers, markets and competitors using ICTs which ultimately affects KM, and this whole scenario signifies the firms’ OI (Umrani, 2016). So in the hospitality industry, the intangible resources, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…RBV demonstrates that business success is heavily reliant on the firm’s resources. These resources are categorized as tangible and intangible capabilities and assets (Umrani, 2016). The framework of this study is mainly based on tangible resources.…”
Section: Theoretical Outlook and Hypotheses Developmentmentioning
confidence: 99%
“…Besides, the literature confirmed that innovation is positively related to a firm's performance (Alosani et al, 2019). Recently, researchers demonstrated that innovation significantly enhances organizational performance in the Pakistani banking sector (Imran et al, 2021). In the environmental context, researchers found that green innovation significantly increases environmental performance (Kraus et al, 2020;Rehman et al, 2021b).…”
Section: Innovativenessmentioning
confidence: 93%